Paul Ricoeur's hermeneutics and the discourse of Mark 13 : appropriating the apocalyptic - Vries, P. de, 1956- (Studies in the thought of Paul Ricoeur, 2016)
This book uses the phenomenological interpretive approach of Paul Ricoeur to shed new light on New Testament eschatological expectation. Peter C. de Vries argues for a metaphorical reading of the apocalyptic discourse of Mark 13, based upon neither the author's intention nor the reader's reception but latent meaning present in the text itself.